ERRATUM: Hydatid cyst involving the mandible ramus - Nivedhitha Maraimalai; Manisha Ahire Sardar; Kavita Wadde; Om Kharat; Shaheen Kanpurwala; Asha Chowdhar (Autopsy and Case Reports, 2023)
Nivedhitha Maraimalai1https://orcid.org/0000-0003-1208-3088, Manisha Ahire Sardar1https://orcid.org/0000-0003-2003-1544, Kavita Wadde2https://orcid.org/0000-0002-0127-0876, Om Kharat3https://orcid.org/0000-0003-1010-691X, Shaheen Kanpurwala4https://orcid.org/0009-0009-1407-651X, Asha Chowdhar2https://orcid.org/0000-0002-3914-9262 How to cite: Maraimalai N, Sardar MA, Wadde K, Kharat O, Kanpurwala S, Chowdhar A. ERRATUM: Hydatid cyst involving the mandible ramus. Autops Case Rep. 2023;13:e2023441. https://doi.org/10.4322/acr.2023.441 1Government Dental College and Hospital, Department of Oral Pathology and Microbiology, Mumbai, India 2Government Dental College and Hospital, Department of Oral and Maxillofacial Surgery, Mumbai, India 3Government Dental College and Hospital, Department of Oral Medicine and Radiology, Mumbai, India 4Grant Government Medical College and Sir JJ Group of Hospitals, Mumbai, India Due to an error in the Affiliations section, the article “Hydatid cyst involving the mandible ramus” (DOI https://doi.org/10.4322/acr.2023.437), published in Autops. Case Rep. 13, 2023, was published with an error. On page affiliations, where the text reads: 4Government Dental College and Hospital, Department of General Pathology, Mumbai, India It should read: 4Grant Government Medical College and Sir JJ Group of Hospitals, Mumbai, India